THE EFFECTIVENESS OF USING COMICSIN TEACHING WRITING NARRATIVE TEXT:AN EXPERIMENTAL STUDY IN THE SECOND GRADE STUDENTS OF A PRIVATE SCHOOL IN BANDUNG - Nur Karunia, - (2011)
Learning writing in English is difficult, and one way to overcome the difficulties is by using comics as teaching aid. This study aims to investigate the effectiveness of using comics in teaching writing narrative text to the second grade students of senior high school, and to find out the advantages and disadvantages of using comics from students' point of view. The data for this quasi experimental study are students' writing scores and questionnaire results, and the writing scores were analyzed with the Mann-Whitney test. The study found that the writing scores of the experimental group and the control group are not significantly different (U=509, ns, p>0.05), however, it is also found that comics have advantages that can help teachers and students to overcome difficulties in learning writing and can be an alternative in teaching narrative writing.